Engaging Bonhoeffer : The Impact and Influence of Bonhoeffer's Life and Thought - Kirkpatrick, Matthew D., 1979- (Book collections on Project MUSE., 2016)
Engaging Bonhoeffer documents the extraordinary impact of Dietrich Bonhoeffer's life and writing on later thought. Despite his lasting legacy, little substantial scholarship has been conducted in this area. In this magisterial collection, leading international scholars fill this striking gap and critically demonstrate the ways in which Bonhoeffer has been one of the most original, inspirational, and provocative writers of the twentieth century. Bonhoeffer's work has proved foundational for a wide variety of thinkers and movements across such areas as ecclesiology, Christology, spirituality, ethics, hermeneutics, phenomenology, epistemology, and systematic theology more generally. Whether one considers his writings to have been faithfully interpreted, critically adopted or justifiably rejected, Engaging Bonhoeffer describes those who have engaged with Bonhoeffer's work, been inspired by his actions, and found a way to express and explain their own ideas through interacting with his life and thought. In addition to shedding light on the different theological trajectories that Bonhoeffer's work may forge, this challenging volume offers a critical window through which to view and appreciate the ideas of many leading voices of modern theology.